A Prototype of Smart Agriculture System Using Internet of Thing Based on Blynk Application Platform - Badri Narayan Mohapatra; Rohan Vilas Jadhav; Ketan Sunil Kharat (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
The research presents the use of the concept of Internet of Things in monitoring the crops and using it in other agricultural purposes. The field of agriculture has always demanded high standards of resources, professionalism and effort. Today majority of the world depends on agriculture for food consumption, economic growth, trade and employment. It also comes with various set of challenges for the agriculturists. Various agriculturists, famers, and scientists across the globe believe in formulating different plans and ideas to deal with these challenges. Smart farming system which is based on fastest growing Internet of Things (IOT) technology which will be cheaper and more productivity and cost effective. In this research we are focusing of handling various information about the crops under consideration and undertake required commands of the user, for a better management of the crops and the resources. Hence providing the agriculturists across various domains a robust and useful capability. Also promoting research and further exploration in the field of use of electronics and internet technology in agriculture.